2016
DOI: 10.1177/2325957416661424
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adherence to Antiretroviral Therapy among People Living with HIV in Coastal South India

Abstract: Background: Antiretroviral Therapy (ART) has transformed life threatening HIV/AIDS scenario into chronic manageable disease. Methodology: In this cross-sectional, 409 People Living with Human Immunodeficiency Virus (PLHIV) aged 18 years, who were on ART, were assessed regarding the adherence to ART and factors affecting adherence using semistructured questionnaire. The association between factors affecting adherence and the level of adherence were analyzed using multiple logistic regression model and odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(50 reference statements)
0
10
1
1
Order By: Relevance
“…9 , 12 , 26 , 27 Similarly at-risk alcohol use has been reported to affect HIV antiretroviral adherence in South India. 28 Notably, having household contacts who drank or had at-risk alcohol use did not predict LTFU, suggesting household alcohol use does not drive adherence. Our findings suggest that in this region of India, high rates of at-risk alcohol use are driving outcomes and may subsequently impact transmission and development of drug resistance.…”
Section: Discussionmentioning
confidence: 98%
“…9 , 12 , 26 , 27 Similarly at-risk alcohol use has been reported to affect HIV antiretroviral adherence in South India. 28 Notably, having household contacts who drank or had at-risk alcohol use did not predict LTFU, suggesting household alcohol use does not drive adherence. Our findings suggest that in this region of India, high rates of at-risk alcohol use are driving outcomes and may subsequently impact transmission and development of drug resistance.…”
Section: Discussionmentioning
confidence: 98%
“…A study done by Banagi et al, showed that patients with the absence of opportunistic infection had shown good adherence to ART. 16 Another study by Joshi et al, also showed that participants without opportunistic infections had good medication adherence. 17 In this study, behaviour, trust and confidentiality among health care workers were significantly associated with medication adherence.…”
Section: Discussionmentioning
confidence: 98%
“…According to a meta-analysis, participants from cohesive families have 1.74 times higher adherence ( 28 ). Yathiraj et al ( 30 ) discovered that participants with a strong family support (74%; OR = 3.0, CI = 1.2, 5.2) were more likely to adhere to ART ( p < 0.05) ( 30 ). According to Joseph et al ( 31 ), family support was statistically associated with high ART adherence ( p < 0.01) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%